Pengaruh Pemberian Daun Sengon (Albizzia falcataria) Hasil Rendaman dengan Larutan Ca(OH)2 Terhadap Bobot Karkas dan Bobot Organ Pencernaan Ayam Pedaging - Akmal, Akmal (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2008)
This  research  aims  at  meauring  the  use  of  Sengon  soaked  in  kapur  tohor  and  is  effect  on  the performance  of  broiler. The  Study  used  100  broiler  Hubber  aged  3  days  and  5  treatments  ration  which contain different sengon. The design used in this study was completely randomized design (CRD) with 5 treatmen.  Parameter  measured were ration consumption, carcas, and digestive tract. The result of this study  shows  that  the  use  of  sengon  in  the  ration  is  effective  segnificantly  (P<0,05)  on  the  ration consumtion, carcass, and  digestive tract. It could be  concluded that sengon can be used up to 7,5% in the ration of the  broiler.